NiM-coated ZSM-5 / Al2O3 catalyst as well as preparation method and application thereof
By using NiM@ZSM-5/Al2O3 catalyst, NiM bimetallic nanoparticles are encapsulated and molded, calcined and reduced, the problems of low catalyst activity and insufficient selectivity in the cracking of high-boiler organic silicones are solved, and high-efficiency high-boiler cracking and chlorosilane monomer selectivity are achieved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202510123351.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-01-26
AI Technical Summary
In the process of cracking the dimethyldichlorosilane in the process of silicone high boiling agent, there are problems such as low catalyst cleavage rate, low selectivity of target products, difficulty in recycling, and limited treatment scale.
Using NiM@ZSM-5/Al2O3 catalyst, the catalyst is prepared by encapsulating NiM bimetallic nanoparticles and by molding, calcining and reduction, which significantly improves the stability and activity of the catalyst, achieving efficient cracking of silicone high boiler and selectivity of chlorosilane monomers.
The high boiler cracking rate exceeds 95%, the selectivity of chlorosilane monomers exceeds 95%, the catalyst stability and selectivity are consistent during long-term use, and are suitable for continuous and stable catalytic reaction systems.
Smart Images

Figure CN119951562A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organosilicon, and in particular to a NiM@ZSM-5 / Al2O3 catalyst and a preparation method and application thereof. Background Art
[0002] With the rapid development of organosilicon monomers, the output of high-boiling substances produced as by-products in the monomer production process has increased sharply, and a large amount of them have accumulated and blocked the warehouse, causing environmental and safety problems, as well as serious waste of resources. At present, organosilicon high-boiling substances have become a problem that restricts the sustainable development of the industry. It is urgent to develop green catalysts for the efficient cracking of organosilicon high-boiling substances to support the green development of the industry.
[0003] At present, tri-n-butylamine is generally used as a catalyst to crack high-boiling products to prepare chlorosilane monomers. Although the operating temperature and pressure are low, there are still fundamental problems that are difficult to overcome. The analysis is as follows:
[0004] (1) The catalyst tri-n-butylamine is a highly toxic chemical and must be strictly controlled during its use cycle and is used as a consumable;
[0005] (2) The selectivity of the target product M2 is low, and the main products are low-value monomethyltrichlorosilane and monomethyldichlorosilane;
[0006] (3) The cracking rate is low, and only chlorine-rich Si-Si can be cracked; the uncracked high-boiling products are mixed with it to form hazardous waste, which further causes secondary pollution to human health and the ecological environment, and wastes resources; the subsequent treatment is more complicated and difficult, and the environmental protection cost is huge;
[0007] (4) In a homogeneous kettle reaction system, it is difficult to separate the product from the catalyst and unreacted raw materials, resulting in poor product purity;
[0008] (5) Kettle reaction system: The processing scale is limited. Under the background of rapid expansion of monomer capacity at this stage, it is urgent to develop a continuous and stable catalytic reaction system.
[0009] The relevant technical patent literature on the preparation of dimethyldichlorosilane by cracking high-boiling organic silicon products is mainly divided into the following methods:
[0010] (1) Precious metal catalysts: CN1071927A, JP54-9228, and JP54-119417 reported the use of precious metals Pd and Pt as catalysts to crack high boiling points, using HCl as the cracking gas source, and requiring toluene or xylene as solvent in a reactor. However, precious metal catalysts are expensive, difficult to recycle, and difficult to purify, making them difficult to apply in large-scale industrial applications.
[0011] (2) Aluminum-based catalysts: US5430168, US5321147, CN1169996A, CN1634937A, CN1634936A, CN1915999A, etc. disclose a method of using aluminum chloride (AlCl3) as a catalyst and HCl as a cracking gas to react in a slurry bed or a fixed bed. Typical process conditions: reaction temperature of 300-500°C, reaction pressure of 4-7MPa, but the M2 yield is low. During the reaction, the active component AlCl3 is easily sublimated and lost, making it difficult to regenerate and recycle the catalyst, and high-pressure operation places stringent requirements on equipment.
[0012] (3) Molecular sieves and activated carbon catalysts: Dow Corning Corporation of the United States uses LZ-Y-74 molecular sieve as a catalyst to crack methylchlorodisilane (Si-Si), with HCl as the cracking gas. To reduce costs, the company chose activated carbon instead of molecular sieves, but the reaction temperature was 500°C higher and the energy consumption was high (see "Resource Utilization of By-Products in the Production of Methylchlorosilane Monomer", Li Bin, master's thesis of Beijing University of Chemical Technology).
[0013] CN115746042A discloses a method for catalytic cracking of high-boiling organic silicon products. The catalyst is a molecular sieve loaded with one or more of Fe, Zn, Ni, Ti, and Mo, but the cracking temperature is high, exceeding 550°C.
[0014] In view of the problems of low catalyst cracking rate, low target product selectivity, difficulty in recycling, and limited processing scale in the reaction of cracking high-boiling silicone products to prepare dimethyldichlorosilane, there is an urgent need to develop a new type of efficient and green catalyst and process for cracking high-boiling silicone products to prepare dimethyldichlorosilane. Summary of the invention
[0015] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a NiM@ZSM-5 / Al2O3 catalyst and a preparation method and use thereof. The NiM bimetallic nanoparticles encapsulated in the catalyst have better stability. The catalyst obtained by molding, calcining and reducing effectively protects the NiM bimetallic nanoparticles, and thus has a better cracking rate and chlorosilane monomer selectivity in the cracking and disproportionation reaction of high-boiling organic silicon.
[0016] To achieve this object, the present invention adopts the following technical solutions:
[0017] In a first aspect, the present invention provides a method for preparing a NiM@ZSM-5 / Al2O3 catalyst, the preparation method comprising the following steps: mixing a NiM@ZSM-5 precursor and an alumina source, and sequentially subjecting the mixture to forming, drying, calcining and reducing to obtain a NiM@ZSM-5 / Al2O3 catalyst; wherein M is a metal other than nickel.
[0018] Compared with the catalysts such as triethylamine, tri-n-butylamine, aluminum powder and the like commonly used in industry, the catalyst provided by the present invention can realize Si-Si and Si-C n (n>4), Si-CH2-Si cleavage bond cleavage, and then realize the directional disproportionation rearrangement of Si, CH3 and Cl functional groups in the chlorosilane monomer obtained by cleavage to obtain higher dimethyldichlorosilane.
[0019] The present invention encapsulates NiM bimetallic materials, and uses the second metal to influence and inhibit the migration and aggregation of Ni nanoparticles during the molding process, thereby ensuring efficient cracking of high-boiling organic silicon products and selectivity of chlorosilane monomers, especially selectivity of dimethyldichlorosilane.
[0020] Preferably, the packaging amount of Ni in the NiM@ZSM-5 precursor is 1.0-5.0wt%, for example, it can be 1.0wt%, 1.5wt%, 1.9wt%, 2.4wt%, 2.8wt%, 3.3wt%, 3.7wt%, 4.2wt%, 4.6wt% or 5.0wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0021] Preferably, the encapsulation amount of M in the NiM@ZSM-5 precursor is 1.0 to 10.0 wt%, for example, it can be 1.0 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt% or 10.0 wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0022] Preferably, said M comprises a non-precious metal.
[0023] Preferably, M comprises any one or a combination of at least two of Co, Mo, Fe, Zn, Mg or Cu, wherein typical but non-limiting combinations are a combination of Co and Mo, a combination of Fe and Mo, a combination of Co and Fe, a combination of Zn and Mo, a combination of Co and Mg, and a combination of Cu and Mo.
[0024] Preferably, the molar ratio of SiO2 / Al2O3 in the NiM@ZSM-5 precursor is 50 to 500:1, for example, it can be 50:1, 100:1, 150:1, 200:1, 250:1, 300:1, 350:1, 400:1, 450:1 or 500:1, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0025] Preferably, the preparation of the NiM@ZSM-5 precursor includes: mixing a silicon source, an aluminum source, a structure directing agent, a Ni source, an M source and water, and sequentially performing hydrothermal crystallization, solid-liquid separation, drying and calcination to obtain the NiM@ZSM-5 precursor.
[0026] Preferably, the silicon source comprises any one of white carbon, silica sol, solid silica gel, water glass or tetraethyl orthosilicate, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of white carbon and silica sol, a combination of solid silica gel and silica sol, a combination of white carbon and solid silica gel, a combination of water glass and silica sol, a combination of white carbon and tetraethyl orthosilicate, and a combination of tetraethyl orthosilicate and silica sol.
[0027] Preferably, the aluminum source includes any one of pseudo-boehmite, SB powder or aluminum sol, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of pseudo-boehmite and SB powder, a combination of aluminum sol and SB powder, and a combination of pseudo-boehmite and aluminum sol.
[0028] Preferably, the structure directing agent comprises any one of n-butylamine, triethylamine, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetramethylethyldiammonium or dimethyldiethylammonium hydroxide, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of tetraethylammonium hydroxide and tetrapropylammonium hydroxide, a combination of tetramethylethyldiammonium and tetrapropylammonium hydroxide, a combination of tetraethylammonium hydroxide and tetramethylethyldiammonium, and a combination of dimethyldiethylammonium hydroxide and tetrapropylammonium hydroxide.
[0029] Preferably, the Ni source comprises a complex solution formed by a nickel-containing compound and ethylenediamine; the nickel-containing compound comprises nickel nitrate, nickel chloride and / or nickel sulfate.
[0030] Preferably, the M source comprises a salt of M.
[0031] Preferably, the M source comprises any one of cobalt nitrate, ammonium molybdate, iron nitrate, zinc nitrate, magnesium nitrate or copper nitrate, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of cobalt nitrate and ammonium molybdate, a combination of iron nitrate and ammonium molybdate, a combination of cobalt nitrate and iron nitrate, and a combination of magnesium nitrate and ammonium molybdate.
[0032] Preferably, the hydrothermal crystallization time is 24 to 96 h, for example, 24 h, 32 h, 40 h, 48 h, 56 h, 64 h, 72 h, 80 h, 88 h or 96 h, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0033] Preferably, the hydrothermal crystallization temperature is 100-170°C, for example, it can be 150°C, 153°C, 155°C, 157°C, 159°C, 162°C, 164°C, 166°C, 168°C or 170°C, but is not limited to the listed values. Other unlisted values within the range are also applicable, preferably 150-170°C.
[0034] Preferably, the calcination temperature is 400-600°C, for example, it can be 400°C, 423°C, 445°C, 467°C, 489°C, 512°C, 534°C, 556°C, 578°C or 600°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0035] Preferably, the calcination time is 4 to 12 hours, for example, 4 hours, 4.9 hours, 5.8 hours, 6.7 hours, 7.6 hours, 8.5 hours, 9.4 hours, 10.3 hours, 11.2 hours or 12 hours, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0036] Preferably, the alumina source comprises any one of pseudo-boehmite, dry glue powder, SB powder or aluminum sol, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of pseudo-boehmite and dry glue powder, a combination of SB powder and dry glue powder, a combination of pseudo-boehmite and SB powder, and a combination of aluminum sol and dry glue powder.
[0037] Preferably, the calcination temperature is 400-700°C, for example, it can be 400°C, 434°C, 467°C, 500°C, 534°C, 567°C, 600°C, 634°C, 667°C or 700°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0038] The present invention preferably controls the calcination temperature within the above range. When the calcination temperature is too high, the basic structure of the material may be damaged.
[0039] Preferably, the calcination time is 4 to 12 h, for example, 4 h, 4.9 h, 5.8 h, 6.7 h, 7.6 h, 8.5 h, 9.4 h, 10.3 h, 11.2 h or 12 h, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0040] Preferably, the calcining atmosphere is any one of air, oxygen, nitrogen or argon, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of air and oxygen, a combination of nitrogen and oxygen, a combination of air and nitrogen, a combination of argon and oxygen, and a combination of air and argon.
[0041] Preferably, the reduction temperature is 400-600°C, for example, it can be 400°C, 423°C, 445°C, 467°C, 489°C, 512°C, 534°C, 556°C, 578°C or 600°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0042] Preferably, the reduction time is 10 to 20 h, for example, 10 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0043] Preferably, the reducing atmosphere is a hydrogen atmosphere.
[0044] In a second aspect, the present invention provides a NiM@ZSM-5 / Al2O3 catalyst, wherein the NiM@ZSM-5 / Al2O3 catalyst is prepared by the preparation method of the NiM@ZSM-5 / Al2O3 catalyst described in the first aspect.
[0045] Preferably, the NiM@ZSM-5 / Al2O3 catalyst comprises a NiM@ZSM-5 active component and an Al2O3 carrier, wherein M is a metal other than nickel.
[0046] Preferably, the Ni content in the NiM@ZSM-5 active component is 1.0-5.0wt%, and the M content is 1.0-10.0wt%, for example, it can be 1.0wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10.0wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0047] Preferably, M comprises any one or a combination of at least two of Co, Mo, Fe, Zn, Mg or Cu, wherein typical but non-limiting combinations are a combination of Co and Mo, a combination of Fe and Mo, a combination of Co and Fe, a combination of Zn and Mo, and a combination of Cu and Mo.
[0048] Preferably, the Ni and M form bimetallic nanoparticles.
[0049] Preferably, the particle size range of the bimetallic particles is 1 to 10 nm, for example, it can be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0050] The preferred particle size of the dual alloy particles of the present invention is within the above range, which has a better catalytic effect.
[0051] Preferably, the content of NiM@ZSM-5 active component in the NiM@ZSM-5 / Al2O3 catalyst is 50-70wt%, for example, it can be 50wt%, 54wt%, 57wt%, 60wt%, 64wt%, 67wt% or 70wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0052] Preferably, the content of Al2O3 in the NiM@ZSM-5 / Al2O3 catalyst is 30-50wt%, for example, it can be 30wt%, 34wt%, 37wt%, 40wt%, 44wt%, 47wt% or 50wt%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0053] The present invention controls the content of the NiM@ZSM-5 active component in the NiM@ZSM-5 / Al2O3 catalyst within the above range. When the content is too high, there is a problem of incomplete encapsulation, and when the content is too low, there is a problem of low catalytic activity.
[0054] In a third aspect, the present invention provides a use of the NiM@ZSM-5 / Al2O3 catalyst described in the second aspect in a cracking and disproportionation reaction of high-boiling organic silicon products.
[0055] The use of the NiM@ZSM-5 / Al2O3 catalyst provided by the present invention in the cracking and disproportionation reaction of high-boiling organic silicon products adopts a fixed bed catalytic process, and the reaction conditions are mild, and the reaction pressure is 0.1-1.5MPa, which is significantly lower than the pressure of the kettle reactor (3-7MPa), greatly reducing the equipment investment cost. The catalyst of the present invention has no loss or addition during use, is green and environmentally friendly, has efficient cracking, and is easy to scale.
[0056] Preferably, the use includes: cracking and disproportionation reaction of high-boiling organosilicon products and cracking gas under the action of NiM@ZSM-5 / Al2O3 catalyst.
[0057] Preferably, the high boiling organic silicon compound comprises Si-Si, Si-CH2-Si, Si-C n (n>4) and other bonds; wherein the Si-Si-containing disilane composition accounts for more than 70%, for example, it can be 71%, 72%, 75%, 78%, 79%, 80%, 81%, 82%, 83%, 84% or 85%, etc.
[0058] Preferably, the cracked gas includes any one of hydrogen, hydrogen chloride or methyl chloride, or a combination of at least two of them.
[0059] Preferably, the temperature of the cracking disproportionation reaction is 250-450°C, for example, it can be 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C or 450°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0060] Preferably, the pressure of the cracking and disproportionation reaction is 0.1 to 1.5 MPa, for example, it can be 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1.0 MPa, 1.2 MPa or 1.5 MPa, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0061] Preferably, the mass space velocity of high boiling products of organosilicon in the cracking and disproportionation reaction is 0.05 to 1.0 h -1 , for example, it can be 0.05h -1 、0.16h -1 , 0.27h -1 , 0.37h -1 、0.48h -1 、0.58h -1 , 0.69h -1 , 0.79h -1 , 0.9h -1 or 1.0h -1 The above values are not limited to the above values, and other values not listed in the above values are also applicable.
[0062] Preferably, the reactor for the cracking and disproportionation reaction comprises any one of a fixed bed, a moving bed, a fluidized bed or a slurry bed.
[0063] The present invention has no special limitation on the solid-liquid separation in the above process. Any device and method for solid-liquid separation known to those skilled in the art can be used, and can also be adjusted according to the actual process, such as filtration, centrifugation or sedimentation separation, or a combination of different methods.
[0064] The present invention has no particular limitation on the drying in the above process. Any drying device and method known to those skilled in the art can be used, and can also be adjusted according to the actual process, for example, it can be air drying, vacuum drying, oven drying or freeze drying, or a combination of different methods.
[0065] Compared with the prior art, the present invention has at least the following beneficial effects:
[0066] (1) The NiM@ZSM-5 / Al2O3 catalyst provided by the present invention encapsulates the NiM bimetallic material, and uses the second metal to influence and inhibit the migration and aggregation of Ni nanoparticles during the molding process, thereby ensuring efficient cracking of high-boiling organic silicon products and selectivity of chlorosilanes;
[0067] (2) The use of the NiM@ZSM-5 / Al2O3 catalyst provided by the present invention in the cracking and disproportionation reaction of high-boiling organic silicon products not only realizes the cracking of low-alkyl Si-Si bonds, but also can realize the cracking of alkyl-rich Si-Si and Si-C n (n>4) and Si-CH2-Si bond cracking, and a fixed bed reactor is used. On the catalyst, high-boiling organic silicon and cracking gas flow through the catalyst bed to carry out gas-solid phase continuous catalytic reaction. Under the preferred conditions, the catalyst has a high-boiling cracking rate of more than 95%, a chlorosilane monomer selectivity of more than 95%, and better catalytic stability. In the life test experiment, the catalyst stably operated for more than 1000h in the laboratory test, and there was no obvious change in the cracking rate and chlorosilane monomer selectivity during the whole process. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 This is the HRTEM image of the NiMg@ZSM-5 / Al2O3 catalyst prepared in Example 2.
[0069] Figure 2 This is the HRTEM image of the NiZn@ZSM-5 / Al2O3 catalyst prepared in Example 3.
[0070] Figure 3 This is the HRTEM image of the Ni@ZSM-5 / Al2O3 catalyst prepared in Comparative Example 1. DETAILED DESCRIPTION
[0071] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0072] Example 1
[0073] This embodiment provides a method for preparing a NiCo@ZSM-5 / Al2O3 catalyst, the preparation method comprising the following steps:
[0074] (1) Preparation of NiCo@ZSM-5 precursor: Referring to the method disclosed in ZL201910092388.5, a silicon source (silica sol), an aluminum source (SB powder), a structure directing agent (tetrapropylammonium hydroxide), a Ni source (a complex solution formed by nickel nitrate and ethylenediamine), an M source (cobalt nitrate) and water are mixed, and the core molar ratio of the obtained mixture is: SiO2:Al2O3:TPAOH:H2O=1:0.003:0.5:30, and the mixture is hydrothermally crystallized at 120°C for 96h, filtered, dried and calcined at 550°C for 10h to obtain the NiCo@ZSM-5 precursor; wherein the Ni content is 4.5wt% and the Co content is 5.2wt%.
[0075] (2) NiCo@ZSM-5 precursor and alumina source (dry rubber powder) were mixed according to a set mass ratio, and the mixture was extruded, dried, calcined at 550 °C in an air atmosphere for 10 h, and reduced at 500 °C in a hydrogen atmosphere for 12 h to obtain a NiCo@ZSM-5 / Al2O3 catalyst. The mass ratio of NiCo@ZSM-5 to Al2O3 was 60:40.
[0076] Example 2
[0077] This embodiment provides a method for preparing a NiMg@ZSM-5 / Al2O3 catalyst, the preparation method comprising the following steps:
[0078] (1) Preparation of NiMg@ZSM-5 precursor: Referring to the method disclosed in ZL201910092388.5, a silicon source (tetraethyl orthosilicate), an aluminum source (pseudo-boehmite), a structure directing agent (tetrapropylammonium hydroxide), a Ni source (a complex solution formed by nickel nitrate and ethylenediamine), a Mg source (magnesium nitrate) and water are mixed, and the core molar ratio of the obtained mixture is: SiO2:Al2O3:TPAOH:Ni:Mg:H2O=1:0.003:0.5:30, and the mixture is hydrothermally crystallized at 170°C for 48h, filtered, dried and calcined at 400°C for 12h to obtain the NiMg@ZSM-5 precursor; wherein the Ni content is 4.5wt% and the Mg content is 4.5wt%.
[0079] (2) A NiMg@ZSM-5 precursor and an alumina source (dry rubber powder) were mixed according to a set mass ratio, and the mixture was extruded, dried, calcined at 700 °C for 4 h in a nitrogen atmosphere, and reduced at 600 °C for 10 h in a hydrogen atmosphere to obtain a NiMg@ZSM-5 / Al2O3 catalyst. The mass ratio of NiMg@ZSM-5 to Al2O3 was 70:30.
[0080] Example 3
[0081] This embodiment provides a method for preparing a NiZn@ZSM-5 / Al2O3 catalyst, the preparation method comprising the following steps:
[0082] (1) Preparation of NiZn@ZSM-5 precursor: Referring to the method disclosed in ZL201910092388.5, a silicon source (solid silica gel), an aluminum source (aluminum sol), a structure directing agent (tetrapropylammonium hydroxide), a Ni source (a complex solution formed by nickel nitrate and ethylenediamine), a Zn source (zinc nitrate) and water are mixed, and the core molar ratio of the obtained mixture is: SiO2:Al2O3:TPAOH:Ni:Zn:H2O=1:0.003:0.5:30, and the mixture is hydrothermally crystallized at 150°C for 96h, filtered, dried and calcined at 600°C for 4h to obtain the NiZn@ZSM-5 precursor; wherein the Ni content is 4.5wt% and the Zn content is 5.7wt%.
[0083] (2) A NiZn@ZSM-5 precursor and an alumina source (aluminum sol) were mixed according to a set mass ratio, and the mixture was extruded, dried, calcined at 400°C in an oxygen atmosphere for 12 h, and reduced at 400°C in a hydrogen atmosphere for 20 h to obtain a NiZn@ZSM-5 / Al2O3 catalyst. The mass ratio of NiZn@ZSM-5 to Al2O3 was 70:30.
[0084] Example 4
[0085] The present embodiment provides a method for preparing a NiCu@ZSM-5 / Al2O3 catalyst, in which cobalt nitrate is replaced by copper nitrate, and the core molar ratio of the obtained mixed material is: SiO2:Al2O3:TPAOH:H2O=1:0.003:0.7:30; the rest is the same as in Example 1 and will not be repeated here.
[0086] Example 5
[0087] The present embodiment provides a method for preparing a NiMo@ZSM-5 / Al2O3 catalyst, in which cobalt nitrate is replaced by ammonium molybdate, and the molar ratio of the obtained mixture is: SiO2:Al2O3:TPAOH:H2O=1:0.003:0.7:30; the rest is the same as in Example 1 and will not be repeated here.
[0088] Example 6
[0089] The present embodiment provides a method for preparing a NiFe@ZSM-5 / Al2O3 catalyst, in which cobalt nitrate is replaced by ferric nitrate, and the molar ratio of the obtained mixture is: SiO2:Al2O3:TPAOH:H2O=1:0.003:0.8:30; the rest is the same as in Example 1 and will not be repeated here.
[0090] Example 7
[0091] This embodiment provides a method for preparing a NiCo@ZSM-5 / Al2O3 catalyst. The preparation method is the same as that of Example 1 except that the calcination temperature is 800°C, and will not be described in detail here.
[0092] Example 8
[0093] This embodiment provides a method for preparing a NiCo@ZSM-5 / Al2O3 catalyst. The preparation method is the same as that in Example 1, except that the mass ratio of the NiCo@ZSM-5 active component to the Al2O3 carrier is 90:10, and thus will not be described in detail.
[0094] Example 9
[0095] This embodiment provides a method for preparing a NiCo@ZSM-5 / Al2O3 catalyst. The preparation method is the same as that in Example 1, except that the mass ratio of the NiCo@ZSM-5 active component to the Al2O3 carrier is 40:60, and thus will not be described in detail.
[0096] Example 10
[0097] The present embodiment provides a method for preparing a NiCo@ZSM-5 / Al2O3 catalyst. The preparation method is the same as that of Example 1, except that in the preparation process of the NiCo@ZSM-5 precursor, only Ni is first encapsulated in situ, and then mixed with cobalt nitrate by an impregnation method and impregnated, and then filtered, dried and calcined at 550°C for 10 hours. The details are not repeated here.
[0098] Compared with the catalyst prepared in Example 1, the catalyst prepared in this example has uneven distribution and non-uniform particle size of NiCo bimetallic nanoparticles, resulting in low catalytic activity in the high-boiling-material cracking reaction.
[0099] Comparative Example 1
[0100] This comparative example provides a method for preparing a Ni@ZSM-5 / Al2O3 catalyst. The preparation method is the same as Example 1 except that cobalt nitrate is not added in step (1), and the details are not repeated here.
[0101] Comparative Example 2
[0102] This comparative example provides a method for preparing a NiCo@ZSM-5 / SiO2 catalyst. The preparation method is the same as Example 1 except that the dry rubber powder in step (2) is replaced by silica sol, and the details are not repeated here.
[0103] Taking Examples 2 to 3 and Comparative Example 1 as examples, HRTEM was used to detect and obtain the following images of the catalysts: Figures 1 to 3 As shown, from Figures 1 to 3 It can be seen that Figures 1-2 There are no obvious metal nanoparticles in the Figure 3 There is obvious removal or agglomeration of metallic nickel nanoparticles.
[0104] The HRTEM analysis method was used to detect the size of the bimetallic particles in the catalyst, the XRF analysis method was used to detect the composition of the catalyst, and the strength of the catalyst was tested using a strength tester.
[0105] The main composition and content of the catalyst in the above examples and comparative examples are shown in Table 1.
[0106] Table 1
[0107]
[0108] The composition of high boiling points of organosilicon in the application example is shown in Table 2.
[0109] Table 2
[0110]
[0111]
[0112] Application Example 1-1
[0113] This application example provides a method for cracking and disproportionating high-boiling organic silicon products, the method comprising:
[0114] Using a fixed bed reactor, high boiling organosilicon products (composition as shown in Table 2) and hydrogen / hydrogen chloride were introduced into a catalyst prepared in Example 1 at a temperature of 320°C, a pressure of 0.3 MPa and a mass space velocity of 0.5 h / min for the high boiling organosilicon products. -1 The cracking reaction is carried out under the conditions of , to obtain a reaction material containing chlorosilane monomer.
[0115] Application Example 1-2
[0116] This application example provides a method for cracking and disproportionating high-boiling organic silicon products. The method is different from application example 1-1 only in that the cracking reaction temperature is 450°C, the pressure is 0.5 MPa, and the feed mass space velocity of the high-boiling organic silicon products is 1.0 h -1 .
[0117] Application Example 2-1
[0118] This application example provides a method for cracking and disproportionating high-boiling organic silicon products, the method comprising:
[0119] A fixed bed reactor was used to introduce high boiling organosilicon products (composition as shown in Table 2) and hydrogen / hydrogen chloride into a catalyst prepared in Example 2 at a temperature of 380°C, a pressure of 0.3 MPa and a mass space velocity of 0.06 h / min. -1 The cracking reaction is carried out under the conditions of , to obtain a reaction material containing chlorosilane monomer.
[0120] Application Example 2-2
[0121] This application example provides a method for cracking and disproportionating high-boiling organic silicon products. The method is different from application example 2-1 only in that the cracking reaction temperature is 450°C, the pressure is 1.0 MPa, and the feed mass space velocity of the high-boiling organic silicon products is 0.1 h -1 .
[0122] Application Example 3-1
[0123] This application example provides a method for cracking and disproportionating high-boiling organic silicon products, the method comprising:
[0124] Using a fixed bed reactor, high boiling organosilicon products (composition as shown in Table 2) and hydrogen / hydrogen chloride were introduced into a catalyst prepared in Example 3 at a temperature of 350°C, a pressure of 0.3 MPa and a mass space velocity of 0.1 h / min for the high boiling organosilicon products. -1 The cracking reaction is carried out under the conditions of , to obtain a reaction material containing chlorosilane monomer.
[0125] Application Example 3-2
[0126] This application example provides a method for cracking and disproportionating high-boiling organic silicon products. The method is different from application example 3-1 only in that the cracking reaction temperature is 450°C, the pressure is 1.0 MPa, and the feed mass space velocity of the high-boiling organic silicon products is 0.3 h -1 .
[0127] Application Examples 4 to 10 and Comparative Application Example 2
[0128] Application Examples 4 to 10 and Application Comparative Example 2 provide a method for cracking and disproportionating high-boiling organic silicon products. The method for cracking and disproportionating high-boiling organic silicon products is the same as Application Example 1-1 except that the catalysts in Examples 4 to 10 and Comparative Example 2 are used respectively, and will not be repeated here.
[0129] Application Comparative Example 1-1
[0130] This application comparative example provides a method for cracking and disproportionating high-boiling organic silicon products. The method for cracking and disproportionating high-boiling organic silicon products is the same as that of Application Example 1-1 except that the catalyst in Comparative Example 1 is used, and will not be described in detail here.
[0131] Application Comparative Example 1-2
[0132] This comparative example provides a method for cracking and disproportionating high-boiling organic silicon products. The method is different from comparative example 1-1 in that the cracking reaction temperature is 450°C, the pressure is 1.0 MPa, and the feed mass space velocity of the high-boiling organic silicon products is 0.15 h -1 .
[0133] Application Comparative Examples 1-3
[0134] This application comparative example provides a method for cracking and disproportionating high-boiling organic silicon products. The method is different from the application comparative example 1-1 only in that the temperature of the cracking reaction is 480°C.
[0135] The reaction materials in the above application examples and application comparison examples were subjected to gas chromatography analysis. The test results of the above application examples and application comparison examples are shown in Table 3.
[0136] Table 3
[0137]
[0138] In Tables 1 to 3, “ / ” indicates that there is no relevant data.
[0139] From Table 1 and Table 2, we can see the following points:
[0140] (1) Comprehensive application examples 1 to 6 show that the NiM@ZSM-5 / Al2O3 catalyst provided by the present invention can form NiM bimetallic particles, and its particle size can be controlled within the range of 1 to 10 nm, and the strength is above 84N. The catalyst is used in the cracking and disproportionation reaction of high-boiling organic silicon products, and the high-boiling product cracking rate is above 95%, preferably above 98%, the chlorosilane monomer selectivity is above 95%, and the selectivity of dimethyldichlorosilane is above 60%;
[0141] (2) It can be seen from Application Example 1-1 and Application Example 7 that the calcination temperature in Application Example 7 is 800°C, and the basic structure of the catalyst is destroyed after calcination at 800°C, resulting in low catalytic activity and selectivity in the high-boiling-substance cracking reaction. This shows that the present invention preferably controls the calcination temperature within a reasonable range, which can further improve the catalytic activity of the catalyst and the selectivity of dimethyldichlorosilane.
[0142] (3) It can be seen from Application Examples 1-1 and Application Examples 8 to 9 that the content of the active component of NiM@ZSM-5 is significantly correlated with the strength and catalytic activity of the catalyst. When the content of the active component of NiM@ZSM-5 is low, the catalytic activity of the catalyst in the high-boiling-substance cracking reaction is low; and when the content of the active component of NiM@ZSM-5 is high, the catalyst strength is poor, resulting in easy pulverization and clogging of the bed during the catalytic process, making it difficult to operate continuously. This shows that the present invention preferably controls the content of the active component of NiM@ZSM-5 within a reasonable range, which can better improve the comprehensive performance of the catalyst.
[0143] (4) It can be seen from Application Example 1-1 and Application Example 10 that in the preparation process of the NiCo@ZSM-5 precursor in Application Example 10, only Ni is encapsulated in situ, and then mixed with cobalt nitrate by impregnation method and impregnated. The particle size distribution and particle size of the obtained NiCo bimetallic particles are uneven, resulting in low catalytic activity in the high-boiling material cracking reaction. This shows that the present invention preferably adopts the method of synchronously encapsulating two metals in situ, which can better improve the catalytic activity.
[0144] (5) It can be seen from the comprehensive application example 1-1 and the application comparison examples 1 to 2 that only single metal Ni is used in the application comparison example 1, resulting in a low conversion rate for high boiling points and low selectivity for chlorosilanes. The application comparison example 2 uses silicon oxide as a carrier, resulting in extremely low strength of the catalyst, making it difficult to use in a fixed bed and unable to operate continuously. This shows that the present invention uses bimetallic particles and uses aluminum oxide as a carrier, has excellent catalytic activity for high boiling points and high selectivity for chlorosilane monomers.
[0145] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a NiM@ZSM-5 / Al2O3 catalyst, characterized in that: The preparation method comprises the following steps: A NiM@ZSM-5 precursor and an alumina source are mixed, and the mixture is molded, dried, calcined and reduced in sequence to obtain a NiM@ZSM-5 / Al2O3 catalyst; Wherein, M is a metal other than nickel.
2. The preparation method according to claim 1, characterized in that: The packaging amount of Ni in the NiM@ZSM-5 precursor is 1.0-5.0wt%; Preferably, the encapsulation amount of M in the NiM@ZSM-5 precursor is 1.0-10.0 wt%.
3. The preparation method according to claim 1 or 2, characterized in that: The M includes non-precious metals; Preferably, the M comprises any one or a combination of at least two of Co, Mo, Fe, Zn, Mg or Cu; Preferably, the molar ratio of SiO2 / Al2O3 in the NiM@ZSM-5 precursor is 50 to 500:
1.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The preparation of the NiM@ZSM-5 precursor comprises: Mixing a silicon source, an aluminum source, a structure directing agent, a Ni source, an M source and water, and sequentially subjecting the mixture to hydrothermal crystallization, solid-liquid separation, drying and calcination to obtain the NiM@ZSM-5 precursor; Preferably, the silicon source includes any one of white carbon black, silica sol, solid silica gel, water glass or ethyl orthosilicate, or a combination of at least two thereof; Preferably, the aluminum source includes any one or a combination of at least two of pseudo-boehmite, SB powder or aluminum sol; Preferably, the structure directing agent includes any one of n-butylamine, triethylamine, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetramethylethyldiammonium or dimethyldiethylammonium hydroxide, or a combination of at least two thereof; Preferably, the Ni source comprises a complex solution formed by a nickel-containing compound and ethylenediamine; the nickel-containing compound comprises a nickel salt and / or nickel hydroxide; Preferably, the M source comprises a salt of M; Preferably, the hydrothermal crystallization time is 24 to 96 hours; Preferably, the temperature of the hydrothermal crystallization is 100-170°C.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The alumina source includes any one of pseudo-boehmite, dry rubber powder, SB powder or aluminum sol, or a combination of at least two thereof; Preferably, the calcination temperature is 400-700°C; Preferably, the calcination time is 4 to 12 hours; Preferably, the calcining atmosphere is any one of air, oxygen, nitrogen or argon, or a combination of at least two of them.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The reduction temperature is 400-600°C; Preferably, the reduction time is 10 to 20 hours; Preferably, the reducing atmosphere is a hydrogen atmosphere.
7. A NiM@ZSM-5 / Al2O3 catalyst, characterized in that: The NiM@ZSM-5 / Al2O3 catalyst is prepared by the preparation method of the NiM@ZSM-5 / Al2O3 catalyst according to any one of claims 1 to 6.
8. The nickel-based bimetallic catalyst according to claim 7, characterized in that: The NiM@ZSM-5 / Al2O3 catalyst comprises a NiM@ZSM-5 active component and an Al2O3 carrier, wherein M is a metal other than nickel; Preferably, the Ni content in the NiM@ZSM-5 active component is 1.0-5.0wt%, and the M content is 1.0-10.0wt%; Preferably, the M comprises any one or a combination of at least two of Co, Mo, Fe, Zn, Mg or Cu; Preferably, the Ni and M form bimetallic particles; Preferably, the particle size of the bimetallic particles ranges from 1 to 10 nm; Preferably, the content of NiM@ZSM-5 active component in the NiM@ZSM-5 / Al2O3 catalyst is 50-70wt%; Preferably, the content of Al2O3 in the NiM@ZSM-5 / Al2O3 catalyst is 30-50wt%.
9. Use of the NiM@ZSM-5 / Al2O3 catalyst according to claim 7 or 8 in the cracking and disproportionation reaction of high-boiling organic silicon.
10. The use according to claim 9, characterized in that The use includes: cracking and disproportionation reaction of high-boiling organic silicon products and cracking gas under the action of NiM@ZSM-5 / Al2O3 catalyst; Preferably, the cracked gas comprises any one of hydrogen, hydrogen chloride or methyl chloride, or a combination of at least two thereof; Preferably, the temperature of the cracking disproportionation reaction is 250-450°C; Preferably, the pressure of the cracking disproportionation reaction is 0.1-1.5 MPa; Preferably, the mass space velocity of high boiling products of organosilicon in the cracking and disproportionation reaction is 0.05 to 1.0 h -1 ; Preferably, the reactor for the cracking and disproportionation reaction comprises any one of a fixed bed, a moving bed, a fluidized bed or a slurry bed.
Citation Information
Patent Citations
Catalyst for preparing light aromatic hydrocarbon by synthetic gas one-step process, and preparation method and application thereof
CN107626343A
Zinc or / and nickel-containing hierarchical structure ZSM-5 molecular sieve and preparation method and application thereof
CN112047358A
Catalytic cracking catalyst as well as preparation method and application thereof
CN118002191A
Catalyst for selective disproportionation and modification of toluene
CN1362391A
Process for ethylene aromatisation from diluted stream
WO2018210826A1